A new methodology for grouping and averaging capillary pressure curves for reservoir models - Mirzaei-Paiaman, Abouzar; Ghanbarian, Behzad (Energy Geoscience, 2021)
Primary drainage capillary pressure data are usually correlatable with a 3D predictable property of grid cells. Accordingly, rock typing is normally performed based on an established correlation. Primary drainage as well as corresponding imbibition and/or secondary drainage capillary pressure curves are averaged to establish a saturation table for each rock type region in reservoir modeling. This study investigates the reliability of this industry-accepted methodology, and has two main contributions. First, we show that if different types of capillary pressures are plotted against water saturation, comparing them might be highly misleading. We demonstrate that although primary drainage capillary pressure data may be plotted against water saturation, the imbibition and secondary drainage capillary pressure data should be plotted against imbibed water saturation. This would enable reservoir engineers to check whether rocks with similar primary drainage capillary pressures do or do not have similar imbibition/secondary drainage counterparts. Using this technique, rock quality can be also deduced from imbibition and secondary drainage capillary pressure curves. We use capillary pressure data measured on limestone and sandstone samples from the Asmari Formation in three Iranian oilfields to evaluate our technique. The second contribution of this study is the proposal of a new methodology for preparing capillary pressure curves for reservoir models. In our methodology, a grid cell can represent more than one rock type region, each specific to a saturation function. As a part of this methodology, we present new physically meaningful equations for averaging primary drainage, imbibition, and secondary drainage capillary pressure curves. [Display omitted] •Relationship of imbibition and secondary drainage capillary pressure data against imbibed water saturation.•A new methodology for preparing capillary pressure tables for reservoir models.•Grid cell representing more than one rock type in a region, each specific to a saturation function.•New equations for averaging capillary pressures curves.